Asymmetric effects of electricity regulatory reforms in the EU15 and in the New Member States: Empirical evidence from residential prices 1990–2011. (August 2015) - Bacchiocchi, Emanuele; Florio, Massimo; Taveggia, Giulia
Abstract: This paper shows that there are asymmetric effects of regulatory reforms within two country groups in the EU. We consider the EU27 countries, and update and enlarge the OECD/ETCR regulatory country indicators up to year 2011. When distinguishing between EU15 countries and New Member States (NMS), we find that market liberalization reduces the price of energy in the EU15 countries, while having the opposite effect for the NMS. The paper concludes that the uniform electricity market reforms in the EU apparently have had different effects between the EU15 and the NMS. This asymmetric shock is not at variance with the principles of market opening, given the different starting points, but may in turn call for different policy responses, as consumers in some NMS have faced significant price increases in a relatively short period of time. Highlights: We show that there are asymmetric effects of electricity regulatory reforms in EU. We consider the EU 27 countries and update the OECD/ETCR regulatory indicators. No effects of privatizion in EU15, while prices increase in the New Member States. Deregulation plays a beneficial role for EU15 countries while a negative one for NMS. Electricity reforms should be evaluated in the perspective of energy poverty in NMS.